تصميم وتقنين اختبار لقياس القدرة العضلية للذراع الحاملة لسلاح الشيش - الساعدي، مصطفى جاسب عبدالزهرة فياض (جامعة ميسان - كلية التربية الرياضية, 2016)
بالنظر لأهمية حركة الذراع الحاملة لسلاح الشيش ودورها الأساسي لإداء المهارات الهجومية والدفاعية لذا يتطلب من المبارز قدرة عضلية لتنفيذها خلال فترة النزال, ومن المعلوم ان اختبار هذه القدرة يعتمد قياسها على المجاميع العضلية للذراعين المسلحة وغير المسلحة (كلتا الذراعين) واذا ما علمنا ان الذراع الغير مسلحة يقتصر واجبها الأساسي على توازن الجسم خلال النزال مما ينعكس ذلك سلباً على نتائج اختبار القدرة العضلية, كما ان الذراع المسلحة هي الاخرى لم يتوفر اختبار يكفلها, ومن هذا المنطلق تبلورت وبرزت مشكلة البحث والتي أراد الباحث السعي لإيجاد الحلول المناسبة لها من خلال تصميم وتقنين اختبار لقياس القدرة العضلية لإداء الذراع المسلحة وتقديم ادق المعلومات التي يمكن الافادة منها لتحقيق الانجاز الامثل في رياضة المبارزة. وهدفت الدراسة الى تصميم وتقنين اختبار لقياس القدرة العضلية لمد وثني الذراع الحاملة لسلاح الشيش, فضلاً عن ايجاد درجات ومستويات معيارية لاختبار القدرة العضلية لمد وثني الذراع الحاملة لسلاح الشيش لدى افراد عينة البحث. حيث تم استخدام المنهج الوصفي, وتكون مجتمع البحث من (20) لاعباً فئة المتقدمين, وبعد أن أكدت نتائج التجارب الاستطلاعية صلاحية الاختبار لذا تم الشروع بإجراء التجربة الرئيسة بتطبيقه. واستنتج الباحث بان الاختبار الذي تم تصميمه وتقنينه اثبت صلاحيته في قياس القدرة العضلية لمد وثني الذراع الحاملة لسلاح الشيش, والدرجات والمستويات المعيارية التي تم الحصول عليها من الاختبار تمثل المستوى الفعلي لأفراد عينة البحث.
The importance given to the carrier arm of the foil and its fundamental role to perform offensive and defensive skills movement therefore requires swordsman muscle's power to implement them during the bout, and it is known to test this ability depends measured the muscle groups of the(both arms) Armed arms and unarmed and if we know that the main duty for unarmed arm is limited to the balance of the body which will reflect negatively on the test results, as the armed arm is the other test guaranteed not available, and from this point of crystallized and emerged as the research problem, which the researcher wanted to seek appropriate solutions through the design and rationing test to measure muscle power to perform arm armed and provide the most accurate information that can utilize them to achieve optimal achievement in the sport of fencing to be a problem with the search. The study aimed to design and codify test to measure the muscular power of the arm carrying the foil; as well as creating a standard grades and levels of research sample. Was used descriptive approach be research community (20) for the player category applicants, and after that the results of the exploratory experiments confirmed the validity of the test; have been initiated to conduct major applied experience. The researcher concluded that the test, which was designed and codified proved its validity in measuring muscle the ability to extend and bend the arm bearing a weapon; and standard grades and levels obtained represent actual level of research sample.
Keywords: رياضة المبارزة -- سلاح الشيش -- القدرة العضلية -- المهارات الهجومية -- المهارات الدفاعية